The Influence of Financial Literacy and Financial Technology on Financial Inclusion Faculty of Islamic Religion Muhammadiyah University of Makassar - Alfina Angraeni; Agusdiwana Suarni; Muhammad Khaedar Sahib (www.amertainstitute.com, 2024)
This study aims to analyze the effect of financial literacy and financial technology on financial inclusion of the Faculty of Islamic Studies, Muhammadiyah University of Makassar. Financial literacy includes financial knowledge, behavior and attitudes in managing finances, while financial technology refers to the use of technological innovation in financial services to improve effectiveness and efficiency. Financial inclusion, as a dependent variable, is defined as an individual's accessibility to formal financial services to improve financial well-being. The study used a quantitative approach with an associative descriptive method. The sample consisted of 77 students selected using the proportionate stratified random sampling technique. Data collection was carried out through a Likert-based questionnaire, which included indicators of financial literacy, financial technology, and financial inclusion. Data were analyzed using multiple regression tests to test the relationship between variables. The results of the study showed that the sig. value. For the effect of X1 on y is 0.169> 0.05 and the t value is 1.388 <t table 1.665, so it can be concluded that H0 is rejected, which means there is no significant effect of X1 on Y and the sig. value. The influence of X2 on y is 0.041 < 0.05 and the calculated t value is 2.079 > t table 1.665, so it can be concluded that H1 is accepted, which means there is a significant influence of X2 on Y.